THE RELATIONSHIP OF SELF EFFICACY AND NURSE'S WORK STRESS IN THE ICU - Renny Triwijayanti; Sandika Sandika; Romiko Romiko; Feby Puryanti (Universitas Muhammadiyah Kudus, 2022)
AbstrakThe highest prevalence of work stress in health workers is experienced by nurses. So that stress can be eliminated properly, this is called self-efficacy . This study aims to determine the relationship between self -efficacy and work stress of nurses in the Inpatient Room. This type of research is a quantitative research with an analytical descriptive research design and uses a cross sectional approach . Samples were taken with a total sampling technique of 48 nurses. Analysis using chi square . The results showed that of the 29 nurses who had high self-efficacy there were 21 respondents (72.4%) who did not experience work stress and 8 respondents who had high self-efficacy experienced work stress. Meanwhile, from 19 nurses who had low self-efficacy , there were 12 respondents (63.2%) who experienced work stress and 7 respondents who had low self-efficacy did not have work stress. There is a relationship between self-efficacy and work stress of nurses. Obtained p Value = 0.032 ( p Value 0.05). it is expected for hospitals to increase self-efficacy by conducting training on positive thinking and forming guidance groups with modeling techniques. And to prevent work stress through exercise, personal refreshing, relaxation techniques and outbound . As well as an evaluation by the hospital management in every nursing action given by the patient.